2012
DOI: 10.1007/s10787-012-0124-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in neurological and psychiatric diseases

Abstract: In recent years, compelling evidence suggests that inflammation plays a critical role in the pathology of a vast number of neurological diseases such as stroke, Parkinson's disease, Alzheimer's disease and amyotrophic lateral sclerosis as well as neuropsychiatric diseases such as major depression and schizophrenia. Despite emerging evidence in human and animal models alike, modulating inflammatory responses have yet to be proven as an effective treatment to prevent or delay the progression of these diseases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 68 publications
0
24
0
1
Order By: Relevance
“…Neuroinflammation occurs in a wide range of brain disorders, from neurodegenerative diseases and central nervous system infection to major depressive disorders, autism, and traumatic brain injury (Glass et al, 2010; Khansari and Sperlagh, 2012; Kolb et al, 1999; Vargas et al, 2005; Ziebell and Morganti-Kossmann, 2010). The opioid antagonist, β-FNA crosses the blood-brain barrier (Labuz et al 2007) and is well-tolerated (Egashira et al 2012; Jang and Yoburn 1991; Valle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation occurs in a wide range of brain disorders, from neurodegenerative diseases and central nervous system infection to major depressive disorders, autism, and traumatic brain injury (Glass et al, 2010; Khansari and Sperlagh, 2012; Kolb et al, 1999; Vargas et al, 2005; Ziebell and Morganti-Kossmann, 2010). The opioid antagonist, β-FNA crosses the blood-brain barrier (Labuz et al 2007) and is well-tolerated (Egashira et al 2012; Jang and Yoburn 1991; Valle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…23 Compelling evidence suggests that persistent inflammation can also result in neurodegenerative and neuropsychiatric diseases, including depression. 21,24,25 Inflammatory cytokines are observed to cross the blood-brain barrier and interact with a number of pathophysiologic mechanisms associated with depression, including neural plasticity, neurotransmitter metabolism, and regulation of the hypothalamic-pituitary-adrenal (HPA) axis. 26 Furthermore, studies have demonstrated that exogenous infusion of cytokines can lead to depressive-like symptoms and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that morphological changes are indicators of microglial activation and inflammation surrounding the amyloid plaques [6]. Activation of astrocytes and microglia and releasing of proinflammatory cytokines and chemokines are the main source of the neuroinflammation [7].…”
Section: Introductionmentioning
confidence: 99%